Visual information processing in recently abstaining methamphetamine-dependent individuals: evoked potentials study - Kremlácek, Jan; Hosák, Ladislav; Kuba, Miroslav; Libiger, Jan; Cízek, Jirí (Documenta ophthalmologica. Advances in ophthalmology, 2008)
OBJECTIVE: Methamphetamine (MAP) is an indirect dopamine agonist that can temporarily increase cognitive performance. However, its long-term abuse may cause dopamine depletion and consequent cognitive and attentional impairment. The worsening of visual functions in Parkinson's disease and their improvement after levodopa administration implicates the role of dopamine in the physiology of vision. This provides the rationale for the investigation of visual functions in abstaining MAP abusers. METHODS: We investigated changes in visually evoked potentials (VEPs) to pattern-reversal and motion-onset stimuli. Such changes serve as indices of visual information processing in the primary and associative areas in a group of recently abstaining MAP abusers (5 females, 18 males, MAP abuse 5.3 +/- 2.8 years) and in 23 age- and gender-paired controls. RESULTS: We did not find differences between the groups in visual acuity. In the group of MAP abusers we observed an attenuation of the early responses around 80 ms and a prolongation of the P1 peak latency after the reversal of high spatial frequency checkerboards (10 and 20 arcmin checks). Furthermore, an attenuation of the latter positive response (170-250 ms) was observed among all the stimuli in parieto-frontal derivations for the MAP abusers. CONCLUSIONS: This is the first report suggesting a slowing and attenuation of VEP responses during visual processing in abstaining methamphetamine abusers.
Keywords: Motion Perception; poruchy spojené s užíváním amfetaminu; zrakové dráhy; mužské pohlaví; Adult; mladý dospělý; Young Adult; Visual Pathways; ženské pohlaví; Humans; methamfetamin; vnímání pohybu; Evoked Potentials, Visual; Amphetamine-Related Disorders; Methamphetamine; dospělí; Female; zrakové evokované potenciály; lidé; Male